PENGARUH KOMPETENSI PEGAWAI TERHADAP KINERJA PEGAWAI DI UNIT KONVEKSI PRIMKOPAD BEKANGDAM III/SLW - Andri Irawan (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2013)
The objective of this research was to know how far the impact competence toward implicationtoward employee’s working method at “ konveksi” unit of Primkopad Bekangdam III/ SLW. The writerhere used Path- Analysis to Analyze the data. Based on the data processing toward the firststructure by using path- analysis, it was found that competition had a impact and significant impact ofworking empolyee’s 26,7%